The Correlation between Total Urine Protein Levels and The Frequency of Hemodialysis in Chronic Kidney Failure Patients - Yusuf, Carla Shafira Angelina; Astuti, Yoni (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2025)
Chronic Kidney Failure (CKF) is a global health problem with a high prevalence, including in Indonesia. Renal replacement therapy, such as hemodialysis, is used to maintain the life of patients with CKF. The study aims to analyze the correlation between total urine protein levels and the frequency of hemodialysis in patients with chronic kidney failure at PKU Muhammadiyah Gamping Hospital from January to September 2023. The research is quantitative and descriptive, using cross-sectional survey methods and secondary data from patient medical records. Statistical analysis uses the Spearman test to test the correlation between variables. Total of HD frequency 1x/week = 6, 2x/week = 58, 3x/week= 1. In order, the trace of protein + 1 = 6, +2 = 58 , +3 = 1. The result of the analysis showed that the total urine protein rate with a frequency of hemodialysis was negatively correlated (r= 0,026; p= 0,84), also did not correlate with gender (r= -0,039; p= 0,756), comorbid (r= -0,038; p= 0,766), and age (r= 0,174; p= 0,166). The conclusion is that there is no correlation between total urine protein levels and the frequency of hemodialysis in patients with chronic kidney failure at PKU Muhammadiyah Gamping Hospital.